Relationship Of Knowledge And Attitude Of Mother In Prevention Of Sexual Transmitted Disease With Gonorrhea In Lau Baleng Village Lau Baleng District, Karo Regency In 2019 - Juli Evianna Purba (Institute of Computer Science (IOCS), 2020)
More than 1 million sexually transmitted diseases (STDs) occur every day. In one year there are an estimated 357 million new sexually transmitted infections (STIs) worldwide. Sexually transmitted disease is a reproductive tract infection (ISR) that is transmitted through sexual contact. This writing aims to determine the relationship between knowledge and attitudes of mothers in preventing sexually transmitted diseases with gonorrhea in Lau Baleng Village, Lau Baleng District, KaroRegency in 2019. The independent variable is knowledge and attitudes of mothers in preventing sexually transmitted diseases and the dependent variable is Gonorrhea. The type of writing used is analytic observational with cross sectional approach method. The population is 210 mothers and the sampling method used in this paper is the Quota Sampling is done by taking the number of samples as much as the number that has been determined by the author, namely 33 mothers. The data used in this writing are primary data through questionnaires and checklists and secondary data obtained from the village head. The statistical test used is the chi-square statistical test α = 0.000. The analysis showed that out of 33 respondents there were 3 people (9.1%) who had good knowledge, 7 people (21.2%) who had sufficient knowledge. And 23 people (69.7%) who have less knowledge. The chi-square statistical results obtained a knowledge value of p = 0.000 and an attitude value of p = 0.000 <α = 0.05, which means that there is a relationship between knowledge and attitudes of mothers in preventing sexually transmitted diseases with gonorrhea. It is hoped that mothers in Lau Baleng Village, Lau Baleng District, Karo Regency in 2019 will increase knowledge about gonorrhea and attitudes in gonorrhea prevention.